Automated guided vehicle (AGV) using 68HC11 microcontroller - Hassan, Zuria Zaidura (2006)
Nowadays the creations of Automated Guided Vehicle (AGV) model can be found from all over the countries, as it give many advantages in our lives. It works just like a robot as it is able to sense and response to the environment. Considering that, AGVs should be well developed to optimize it’s benefits to our own living. The aim of this project is to build a prototype of an Automated Guided Vehicle (AGV) model that can move on a flat surface with its two driving wheels and a free wheel. The prototype is able to follow line on floor with the M68HC11 microcontroller as it main brain that control all the navigation and responses to the environment. The ability to follow line on floor is an advantage of this prototype as it can be further developed to do more complicated task in real life. To follow the line, the microcontroller is attached to a sensor that continuously reflecting to the surface condition. Therefore, this project involves of designing and fabrication of the hardware and circuitry. The key study in this project is the algorithm designed in assembly language, embedded in the microcontroller.